Inovasi Pupuk Cair: Pupuk Limbah Tankos Buah Sawit (PLTBS) dalam Meningkatkan Kesuburan Tanah dan Tanaman - Syafrida Hani; Hasbi Assiddiq; Adrian Bagas; Dodo Wiranda; Sitta Hazzar Eka Romadhon (Universitas Batanghari Jambi, 2022)
Utilization of waste from oil palm fruit tanks as the basic material for making liquid fertilizer is an embodiment of love for the environment. Tankos waste which has been scattered into garbage, turns out to have content that is useful for increasing soil fertility. Through the process of burning and mixing with materials in the form of urea, KCl, EM4 and water, which are then fermented to produce liquid fertilizer that has a selling value. The results of the content test for PLTBS liquid fertilizer provide information about the advantages of PLTBS products, which can accelerate plant growth, increase chlorophyll levels and photosynthesis rate, so that leaves become denser and plants are healthier. The content of PLTBS fertilizer solution can also improve soil chemical properties and suppress pest and disease populations, thereby increasing fruit production and plant fertility. When compared to competitors, the price of PLTBS products is very affordable and much cheaper than other liquid fertilizer products. This product also supports going green because it is environmentally friendly and does not contain harmful ingredients. Based on the business feasibility projection, the PLTBS liquid fertilizer product is feasible to run, besides being able to increase income, it can also create jobs.